Taxonomic resolution of the North American invasive species of the genus Bythotrephes Leydig, 1860 (Crustacea: Cladocera: Cercopagididae) - Korovchinsky, Nikolai M.; Arnott, Shelley E. (Zootaxa, 2019)
The invasive species of the genus Bythotrephes introduced in the North American lakes in 1970s-early 1980s was named variously either B. cederstroemi or B. longimanus. The investigation of individuals of the genus from 15 Canadian lakes has allowed us to identify all of them as B. cederströmii Schödler, based on the detailed taxonomic redescription of the Eurasian representatives of the species. The available documented data (figures and photographs) on Bythotrephes from other North American lakes, made it possible to recognize their identity with this species as well. The possible introduction of interspecific hybrids of the genus Bythotrephes in the North American lakes has not been confirmed.